Development and external validation of a nomogram with inflammatory markers for predicting invasiveness of intraductal papillary mucinous neoplasm of pancreas. Issue 11 (18th March 2022) - Yoon, So Jeong; Kim, Hongbeom; Lee, Okjoo; Jung, Ji Hye; Lim, Chang-Sup; Shin, Yong Chan; Kwon, Wooil; Jang, Jin-Young; Shin, Sang Hyun; Heo, Jin Seok; Han, In Woong
Abstract : Abstract: Recent studies have reported that inflammatory markers, such as neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and advanced lung cancer inflammation index, are associated with invasiveness of intraductal papillary mucinous neoplasm (IPMN). This study aimed to develop and validate a new nomogram that includes inflammatory markers for predicting the invasiveness of IPMN. The data of 365 patients who underwent surgical resection for IPMN at 4 centers between 1995 and 2016 were retrospectively reviewed to develop a new nomogram. For external validation, a separate patient cohort was used. The predictive ability of the nomogram was evaluated using the area under the receiver operating characteristic curve. The new nomogram was developed using the following variables which were identified as risk factors for invasive IPMN: body mass index, preoperative serum bilirubin level, carbohydrate antigen 19-9, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, advanced lung cancer inflammation index, main duct type, presence of solid portion, and tumor size. After external validation, the area under the curve value was 0.649 (95% CI: 0.578-0.720, P < .001). To the best of our knowledge, this study is the first to predict and externally validate the invasiveness in IPMN using inflammatory markers. Further research is necessary to improve predictability of the model for selecting patients for surgical resection.